Metode Forward Chaining untuk Diagnosa dan Penanganan Penyakit Stroke dengan Sistem Pakar - Rhima Diana; Ryci Rahmatil Fiska (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research aims to develop a web-based expert system with the Forward Chaining method that can diagnose and provide treatment for people with stroke disease. The expert system will be used to help the diagnosis process by analyzing the symptoms reported by the patient. The Forward Chaining method will be used as an inference approach in this expert system. The system will use a knowledge base that contains medical rules obtained from experts. The inference process will be carried out by linking the symptoms reported by the patient with the information in the knowledge base to determine possible diagnoses and appropriate treatments. This expert system will be implemented in the form of a web-based application that can be accessed by the general public. The results of this study show that the expert system to diagnose and provide treatment using the forward chaining method is successfully built and the application can be used to help the general public diagnose by entering the symptoms felt and the expert system will provide diagnostic results and provide treatment.